Synthesis of Nanoscale Calcium Silicate Hydrate for Strength Enhancement of Cement Paste - Ming Wang (AIDIC Servizi S.r.l., 2021)
Calcium silicate hydrate-polycarboxylate (C-S-H-PCE) nanocomposites can greatly increase the hydration speed of cement paste. To obtain the optimal synthesis condition for smaller particle size, C-S-H-PCE was prepared by adding Ca(NO3)2(4H2O and Na2SiO3(5H2O solution into PCE dispersion solution under high speed stirring, and the effects of reaction temperature, drip flow rate, aging time, C-S-H content and molecular weight of PCE on the particle size distribution of C-S-H were studied. Dynamic light scattering (DLS) and transmission electron microscopy (TEM) were employed to conduct the analysis of particle size and morphology of the prepared C-S-H-PCE. The application performance of the nano composite was characterized by testing the compressive strength of cement paste added with C-S-H-PCE. The experimental results showed that at 25 ?, C-S-H-PCE synthesized with lower PCE molecular weight, slower drip flow rate, and smaller C-S-H content had better performance. The compressive strength of cement paste with C-S-H-PCE cured under low temperature condition was tested. It turned out that the prepared nanocomposites can remarkably enhance the early strength of cement paste for up to 63.8 % and 24.2 % after 1 d and 3 d.